How Many Bucks in a Bang: On the Estimation of the Economic Costs of Conflict - Olaf J. de Groot; Tilman Brück; Carlos Bozzoli (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
The estimation of the costs of conflict is currently receiving a lot of attention in the literature. This paper aims to give a thorough overview of the existing literature, first by addressing the history of case studies that address conflict costs and second by looking at the existing body of cross-country analyses for conflict costs. In addition to the existing cross-country literature, a number of studies that only concern themselves with particular elements of conflict costs are included as well. In the end, this paper combines the insights from these previous analyses to explore how much room there is to further improve the existing studies. Specific recommendations are given how to proceed with the development of the field of conflict cost measurement.
Keywords: C20; F50; O11; 330; Conflict; costs of conflict; case studies